Faktor-Faktor Yang Mempengaruhi Minat Menggunakan E- Money Flazz BCA di Kabupaten Tangerang - Dwiki Zarasky; Lies Handrijaningsih; Anisah Anisah; Septi Mariani Tis A. Ramadhani (Jurnal Doktor Manajemen (JDM), 2022)
ABSTRACTTechnological support for innovation brings changes in people's needs for a payment instrument that can meet speed, accuracy, and security in every electronic transaction. The electronic payment system or payment with electronic money (e-money) is influenced by advances in technological developments and changes in people's lifestyles. This study aims to determine the trust, social influence, and perceived benefits of the interest in using BCA E-Money Flazz in Tangerang City. Methods of data collection using questionnaires. The data of this research are primary, the determination of the sample uses a purposive sampling technique, and the respondents are consumers of e-money Flazz BCA in Tangerang City. The analytical tools in this study consist of; validity test, reliability test, classical assumption tests, multiple linear regression, t test, F test, and determination test. Processing the results of the questionnaire in this study using SPSS (Statistical Product and Service Solutions). The results showed that trust, social influence, and perceived benefits influenced the interest in using partially and simultaneously on the interest in using e-money.Keywords: Trust, Social Influence, Perception of Benefits, Interest in Using.